Assessment of some health parameters in West African Pygmy Goats and Cameroon Dwarf Sheep of a Zoo in Greece - TAHAS (Σ.Α. ΤΑΧΑΣ) S. A.; GIADINIS (Ν.Δ. ΓΙΑΔΙΝΗΣ) N. D.; KRITSEPI-KONSTANTINOU (Μ. ΚΡΙΤΣΕΠΗ-ΚΩΝΣΤΑΝΤΙΝΟΥ) M.; PAPADOPOULOS (Η.ΠΑΠΑΔΟΠΟΥΛΟΣ) E.; PETRIDOU (Ε.Ι. ΠΕΤΡΙΔΟΥ) E. J.; POSANTZIS (Δ. ΠΟΣΑΝΤΖΗΣ) D.; DOVAS (ΔΟΒΑΣ Χ.Ι.) C. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Ten A frican pygmy goats and five Cameroon sheep from the Attica Zoological Park in Greece were examined for some health parameters including a thorough clinical examination, haematology, serum biochemistry, serological and P CR examination for small ruminant lentivirus, milk bacteriology for common pathogens of clinical or subclinical mastitis and faecal parasitology. These were compared with the existing literature for these two exotic breeds of small ruminants. Haematologic and biochemistry values are compared to existing literature for the pygmy goats whereas this is the first report of such values in Cameroon sheep. A ll animals proved clinically healthy and were free of common pathogens found in small ruminants in Greece as well as for intestinal and respiratory parasites